FOREIGN EXPERIENCES IN IMPROVING THE METHODOLOGY OF PREPARING STUDENTS FOR PROFESSIONAL ACTIVITY (International Educators Conference, 2025)
The article examines foreign experiences in improving the methodology of preparing students for professional activity, highlighting innovative approaches and best practices adopted by various countries. Emphasis is placed on competencybased education, integration of digital tools, industry collaboration, and the development of soft skills to align education with the demands of the modern workforce. Examples from nations such as Germany, Finland, Singapore, and the Netherlands illustrate the effectiveness of personalized learning, dual education systems, and technological advancements in bridging the gap between academic learning and practical application. The study also explores challenges, such as socioeconomic disparities and outdated educational frameworks, and provides insights into strategies for fostering lifelong learning and inclusive educational practices. The findings underscore the importance of flexibility, industry relevance, and holistic assessment in equipping students with the skills and mindset required for professional success in a rapidly changing global landscape.a